2011
DOI: 10.1074/jbc.m110.166959
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of Human MRP1 (ABCC1) Is Dependent on Amino Acids in Cytoplasmic Loop 5 and Its Interface with Nucleotide Binding Domain 2

Abstract: , and Gly 511 had no effect on MRP1 levels. Except for K503A, however, transport by these mutants was reduced by 50 to 75%, an effect largely attributable to reduced substrate binding and affinity. Studies with 32 P-labeled azido-ATP also indicated that whereas ATP binding by the G511I mutant was unchanged, vanadate-induced trapping of azido-ADP was reduced, indicating changes in the catalytic activity of MRP1. Together, these data demonstrate the multiple roles for CL5 in the membrane expression and function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 48 publications
2
44
1
Order By: Relevance
“…MRP1 is a glycoprotein known as ABCC1 and belongs to the ATP-binding protein superfamily [8] . This molecule has three membrane-spanning domains and two nucleotide-binding domains, which function as the ATP-dependent drug pump that effluxes drugs and organic anions across the plasma membrane [4,9] .…”
Section: Discussionmentioning
confidence: 99%
“…MRP1 is a glycoprotein known as ABCC1 and belongs to the ATP-binding protein superfamily [8] . This molecule has three membrane-spanning domains and two nucleotide-binding domains, which function as the ATP-dependent drug pump that effluxes drugs and organic anions across the plasma membrane [4,9] .…”
Section: Discussionmentioning
confidence: 99%
“…The generation of wild-type, K513A, K516A, E521A, and E535A mutant MRP1 pcDNA3.1 expression vectors has been described previously (19,21). The expression vectors (20 g of DNA) were transfected into 90 -95% confluent SV40-transformed human embryonic kidney cells (HEK293T) using Lipofectamine 2000 (Invitrogen).…”
Section: Transfections Preparation Of Membrane Vesicles and Measurementioning
confidence: 99%
“…Inspection of homology models of MRP1 showed that three of the four latter charged residues are predicted to lie at the interface of CL5 with NBD2 (see Fig. 1B) (11,19), and selected mutations in NBD2 allowed us to conclude that bonding interactions between CL5 and NBD2 play a pivotal role in the proper folding and assembly and, hence, expression of MRP1 at the plasma membrane. Our findings also demonstrated that interactions of the fourth amino acid, Glu 535 , with certain amino acids in CL5 and CL6 were important for efficient expression of MRP1 in mammalian cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations